ASSISTANCE IN EXIT SITE CARE FOR PATIENTS WITH CONTINUOUS AMBULATORY PERITONEAL DIALYSIS (CAPD) CATHETER INSTALLATION - Utami, Yulian Wiji; Ulfa, Kholifatu; Fatma, Endah Panca Lydia; Dewi, Elvira Sari (Caring: Jurnal Pengabdian Masyarakat, 2023)
Chronic kidney failure, a progressive and irreversible decline in kidney function, poses a significant health challenge with diverse etiologies. Continuous Ambulatory Peritoneal Dialysis (CAPD) emerges as a crucial treatment method, utilizing the peritoneal cavity as a conduit for dialysis fluid. Prolonged CAPD use, coupled with inadequate maintenance, can lead to peritoneal membrane failure, resulting in complications such as peritonitis. This community engagement initiative aims to enhance patient adherence to exit site care at home for CAPD users, mitigating the risk of recurrent peritonitis infections. Patient data were sourced from the CAPD Center at Dr. Saiful Anwar Hospital in Malang. Preventive efforts focused on empowering patients through routine exit site care modules delivered at home. Notably, 83% of respondents exhibited high adherence to exit site care, signifying a positive impact on infection prevention. Additionally, the majority of CAPD patients reported good quality of life at 67.9%. This study interprets adherence as patients' behavior aligning with Standard Operational Procedures post-consultation, with 83% demonstrating compliance. The findings underscore the importance of home-based exit site care in reducing recurrent peritonitis incidents among CAPD patients.